Novel oil extraction technologies: Process conditions, quality parameters, and optimization. Issue 1 (4th December 2019) - Mwaurah, Peter Waboi; Kumar, Sunil; Kumar, Nitin; Attkan, Arun Kumar; Panghal, Anil; Singh, Vijay Kumar; Garg, Mukesh Kumar
Abstract: Conventional techniques of extracting oil using organic solvents pose health, safety, and environmental concerns. In modern extraction methods, green solvents such as water, ethanol, ethyl acetate, carbon dioxide, ionic liquids, and terpenes are currently gaining prominence. These green solvents present no signs of pollution and remain in liquid form over a temperature range of 0 to 140 °C. Other techniques covered in this review include microwave‐assisted enzymatic extraction, ultrasound‐assisted extraction, supercritical fluid technology, high pressure–assisted extraction, and pulse electric field–assisted extraction. These techniques are considered environmentally friendly because they exhibit less hazardous chemical synthesis, use renewable feedstock, and reduce the chemical load and emissions generated by organic solvents. Aqueous enzymatic extraction is a novel technique that uses enzymes as the medium for extraction of oil. Selection of the enzymes solely depends on the structure of the oilseed and the composition of the cell wall. Studies reveal an enzyme to substrate ratio of 1% to 8%, the temperature of 40 to 55 °C, and a pH of 4 to 8 to be typical for enzymatic extraction of oil from different oilseeds. Microwave‐assisted extraction has proven to impart significant effects on mass transfer and offers high throughput and extraction efficiency. A microwave power of 275 to 1, 000 W and a temperature range of 30 to 60 °C are noticed in the different studies. The review presents a comprehensive account of the modern extraction techniques, the parameters responsible for yield and quality, and their industrial applications. Besides, the review highlights the optimized parameters for oil extraction from different oil‐bearing materials.